A note on income elasticity of health care expenditure in the regions of Mexico - Sáenz-Vela, Hada M.; Guzmán-Giraldo, Ángela M. (Estudios Económicos de El Colegio de México, 2022)
In Mexico, out of pocket health expenditure has a considerable association with income and behaves differently between regions. With information at individual level for the period 2008 to 2018 and Tobit models, the temporal and geographical changes of the income elasticity of private spending on health are analyzed. In the North region it persists as a luxury good, while in Central and South zones it fluctuates around the unit value. It seems that the structural regional divergences are being reflected in the possibilities of using the income in items of sanitary expenses in the households.